2010
DOI: 10.1200/jco.2009.26.6791
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Window Study on Rituximab in Newly Diagnosed Pediatric Mature B-Cell Non-Hodgkin's Lymphoma and Burkitt Leukemia

Abstract: Rituximab is active as a single-agent in pediatric B-NHL even though the RR was lower than requested in the phase II plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 27 publications
1
115
0
2
Order By: Relevance
“…Among this group, 64% of patients with BL had a complete or partial response (Griffin et al, 2009). Meinhardt et al (2010) published the results of a pilot window study investigating the upfront usage of rituximab in children with newly diagnosed mature B cell NHL and Burkitt leukaemia. This study demonstrated an approximately 42% response rate to single agent rituximab in children with newly diagnosed, advanced mature B cell lymphoma (Meinhardt et al, 2010).…”
Section: Immunotherapymentioning
confidence: 99%
“…Among this group, 64% of patients with BL had a complete or partial response (Griffin et al, 2009). Meinhardt et al (2010) published the results of a pilot window study investigating the upfront usage of rituximab in children with newly diagnosed mature B cell NHL and Burkitt leukaemia. This study demonstrated an approximately 42% response rate to single agent rituximab in children with newly diagnosed, advanced mature B cell lymphoma (Meinhardt et al, 2010).…”
Section: Immunotherapymentioning
confidence: 99%
“…Mature B-cell ALL (also called Burkitt leukemia) is rare, accounting for only about 2% to 3% of childhood ALL [Meinhardt et al, 2010].…”
Section: List Of Figuresmentioning
confidence: 99%
“…The feasibility of rituximab was also explored recently in newly diagnosed pediatric patients with mature B-cell NHL and Burkitt leukemia. 23 Rituximab in younger patients with CD20 ϩ B-precursor ALL…”
Section: Rituximab In Mature B-all and Burkitt Nhlmentioning
confidence: 99%